2020
DOI: 10.1016/j.ebiom.2020.102953
|View full text |Cite
|
Sign up to set email alerts
|

Quantification, epitope mapping and genotype cross-reactivity of hepatitis B preS-specific antibodies in subjects vaccinated with different dosage regimens of BM32

Abstract: Background Chronic hepatitis B virus (HBV) infections are a global health problem. There is a need for therapeutic strategies blocking continuous infection of liver cells. The grass pollen allergy vaccine BM32 containing the preS domain of the large HBV surface protein (LHBs) as immunogenic carrier induced IgG antibodies in human subjects inhibiting HBV infection in vitro . Aim of this study was the quantification, epitope mapping and investigation of HBV genotype cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 36 publications
1
24
0
2
Order By: Relevance
“…In the meantime, the BM32 vaccine has been shown to be clinically effective in a multicenter DBPC phase IIb study [ 64 ] (Table 1 ) and is scheduled for phase III studies. The analysis of sera from a recent phase IIb study confirmed the robust induction of IgG antibodies against the domain of PreS, which is critical for the binding of the HBV virus to liver cells and demonstrated cross-reactivity with the most common HBV strains [ 65 ▪▪ ] (Table 1 ). Thus PreS-based allergy vaccines may be useful for vaccination against HBV.…”
Section: Recombinant Hypoallergenic Moleculesmentioning
confidence: 96%
“…In the meantime, the BM32 vaccine has been shown to be clinically effective in a multicenter DBPC phase IIb study [ 64 ] (Table 1 ) and is scheduled for phase III studies. The analysis of sera from a recent phase IIb study confirmed the robust induction of IgG antibodies against the domain of PreS, which is critical for the binding of the HBV virus to liver cells and demonstrated cross-reactivity with the most common HBV strains [ 65 ▪▪ ] (Table 1 ). Thus PreS-based allergy vaccines may be useful for vaccination against HBV.…”
Section: Recombinant Hypoallergenic Moleculesmentioning
confidence: 96%
“…For other viruses (eg, hepatitis B, HBV), unfolded surface antigens have been found to induce protective antibodies and virus attachment can be blocked with unfolded peptides derived from the viral receptor‐binding site. 14 , 15 , 16 For SARS‐CoV‐2, it is not yet known if antibodies toward sequential or conformational epitopes or both determine the neutralizing activity of the natural polyclonal antibody response.…”
Section: Introductionmentioning
confidence: 99%
“…a 3 HBsAg-Proteine (S, M, L) adw [ 35 , 36 ] 2001 Hepagene®, Medeva (n.v.) 3 HBsAg-Proteine (S, M, L) adw und ayw [ 2 , 37 ] Neue Konzepte 2016 BM32®, Viravaxx (exp.) PräS-Graspollenallergen Fusionsprotein [ 38 , 39 ] Al. Aluminium, exp.…”
Section: Entwicklung Der Gentechnisch Hergestellten Hepatitis-b-impfstoffeunclassified
“…Als erfreulichen Nebeneffekt der Immunisierung von allergischen Probanden mit ihrem experimentellen Impfstoff BM32 ® fand die Gruppe im Jahr 2016 HBV-neutralisierende Anti-PräS1-Antikörper [ 38 ]. Bei weiteren Probanden wurde gezeigt, dass diese Antikörper tatsächlich gegen die Rezeptorbindungsstelle im PräS1 gerichtet sind und mit allen HBV-Genotypen von A bis H reagieren [ 39 ]. Da es schon erste Erprobungen im Menschen mit Graspollenallergie gibt, sollten nunmehr spezielle Studien zur Schutzwirkung gegen HBV-Exposition möglich sein.…”
Section: Perspektiven Für Bessere Hb-impfstoffeunclassified